THE ART OF WORDPLAY: DECONSTRUCTION AND DIFFÉRANCE IN LEWIS CARROLL’S SYLVIE AND BRUNO - Rachel, D Cynthia; Vennila, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lewis Carroll, who is best known for his Alice novels, is also the author of a lesser known but equally captivating novel named Sylvie and Bruno. This novel, set in both the real world and a fantastical fairyland, is filled with nonsensical phrases, puns and paradoxes which serves to challenge the reader’s understanding and perception of language. In Carroll’s imaginary world, language and words do not necessarily have fixed meanings and are fluid and open to interpretation. This aligns with the critical concept of deconstruction, pioneered by the French philosopher Jacques Derrida, stating that language and meaning are inherently unstable and texts can contain contradictory meanings. Further, the concept of différance, which is integral to Derrida’s idea of deconstruction, reflects on the fluid nature of text and meaning. In Sylvie and Bruno, Carroll’s clever manipulation of language and meaning can be examined through the lens of deconstruction and différance, thereby revealing the arbitrary nature of language. This research paper aims to analyze how Carroll’s manipulation of words, language and meaning reflects Derrida’s critical approach of deconstruction, particularly the fluidity and unpredictability of language and meaning.